Mango (cv. Nam Dokmai) peel as a source of pectin and its potential use as a film-forming polymer - Tanpong Chaiwarit (2020)
© 2019 Elsevier Ltd Pectin from mango peel (MP) was extracted and studied by analytical and physicochemical methods in comparison to low methoxyl pectin (LMP). The results revealed that MP contained 68% galacturonic acid, and its degree of esterification determined by titration and 1H NMR were 76% and 79%, respectively. For water sorption kinetics, LMP exhibited higher adsorption capacity than MP, as shown by the Guggenheim–Anderson–de Boer model. Both pectin types displayed Brunauer type II adsorption behavior. Thin films were then produced from the extracted MP and characterized. The thin film fabricated from LMP and MP at 1:2 ratio with 40% (w/w) glycerol attained the highest elongation at break (8.80%) and lowest Young's modulus (83.19 MPa). When the MP ratio was increased, the water contact angle of the films tended to increase due to the increased hydrophobicity. Overall, this study found that mango peel waste can be used as a source of pectin and this pectin can be regarded as a potential biopolymer for film formulation as drug delivery systems or edible film for food packaging.